2022
DOI: 10.2147/dddt.s334415
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Combined with Femoral Nerve Block Provides Effective Analgesia Similar to Femoral Nerve Combined with Sciatic Nerve Block in Patients Undergoing Total Knee Arthroplasty: A Randomized Controlled Study

Abstract: Background: Total knee arthroplasty (TKA) is a severe traumatic procedure, and femoral nerve block (FNB) combined with a sciatic nerve block (SNB) is widely used in TKA. However, injury of the sciatic nerve is clinically reported. Dexmedetomidine (DEX) could reduce stress and inflammation, as well as improve pain in TKA. This study aims to observe the analgesic impact of DEX combined with FNB in TKA. Methods: Eighty-eight patients undergoing TKA were included and randomly divided into two groups: DF group (FNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
2
Order By: Relevance
“…Xiao et al 72 compared the difference between femoral and sciatic nerve blocks. The results indicated that the analgesic effect of dexmedetomidine combined with femoral nerve block in TKA was similar to that of femoral-sciatic nerve block.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 99%
“…Xiao et al 72 compared the difference between femoral and sciatic nerve blocks. The results indicated that the analgesic effect of dexmedetomidine combined with femoral nerve block in TKA was similar to that of femoral-sciatic nerve block.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 99%
“…Namun, banyak studi menetapkan bahwa dosis aman maksimum dexmedetomidine adalah 2 μg/kg. Namun, menurut penelitian terbaru oleh (Xiao et al, 2022), dosis 1 μg/kg dexmedetomidine memberikan keseimbangan yang otimal antara analgesia pascaoperatif yang memadai dan efek samping dari blok saraf perifer.\ Penelitian sebelumnya menunjukkan bahwa dosis dexmedetomidine berpengaruh pada efeknya di sekitar area yang diolah, dengan dosis 100 μg dexmedetomidine menunjukkan peningkatan waktu blok yang signifikan. Meskipun banyak studi menetapkan dosis aman maksimum dexmedetomidine adalah 2 μg/kg, penelitian terbaru menyarankan bahwa dosis 1 μg/kg dexmedetomidine memberikan keseimbangan optimal antara analgesia postoperatif dan efek samping blok saraf perifer.…”
Section: Pendahuluanunclassified
“…Sedangkan efek perifer dexmedetomidine bergantung pada dosis, dan 100 μg dexmedetomidine memiliki keunggulan lebih dalam memperpanjang waktu blok. Banyak penelitian menetapkan bahwa dosis maksimal aman dexmedetomidine adalah 2 μg/kg (Vorobeichik et al, 2017;Xiao et al, 2022). Oleh karena itu, dosis dexmedetomidine 1 μg/kg memberikan keseimbangan optimal antara analgesia postoperatif yang memadai dan efek samping blok saraf perifer (Xiao et al, 2022).…”
Section: Rekomendasi Dalam Peripheral Nerve Blockunclassified
“…In a noninferiority randomized controlled trial with 88 patients undergoing elective total knee arthroplasty (TKA), Xiao et al 1 showed that dexmedetomidine (Dex) combined with femoral nerve block (FNB) provided similar analgesic efficacy to FNB combined with sciatic nerve block (SNB). Other than the limitations described in the discussion, however, we noted other issues in the design and results of this study that deserve further discussion and clarification.…”
Section: Dear Editormentioning
confidence: 99%